The Influence of School Culture, Transformational Leadership, and Teacher Motivation on Teacher Performance - Berek, Yanuarius Tasik; Irsan, Irsan; Lubis, Joharis (RIRAI Publisher, 2024)
The purpose of this study is to ascertain the following: (1) the impact of school culture on junior high school work motivation; (2) the impact of transformational leadership on this relationship; (3) the impact of school culture on junior high school teacher performance; (4) the relationship between transformational leadership and junior high school performance; and (5) the impact of work motivation on junior high school teacher performance. Using descriptive data analysis methodologies, the study was carried out at junior high schools in the Delitua District in the academic year of 2023–2024. Regression analysis techniques were included in the data analysis method. There is a sample of 128 teachers in the population. The study's findings demonstrated that: (1) work motivation is directly impacted by school culture; (2) work motivation is directly impacted by transformational leadership in a significant positive way; (3) school culture directly affects performance; (4) transformational leadership directly affects performance; and (5) work motivation directly affects performance. These findings suggest that teacher effectiveness is influenced by school culture, transformational leadership, and work motivation and are important factors in supporting teacher performance.